Red Hat Enterprise Linux 5 administration unleashed - Fox, Tammy, 1964- (Sams, 2007)
A guide to Red Hat Enterprise Linux 5 administration covers such topics as streamlining deployment with Kickstart, managing storage, administering users and groups, scripting and scheduling tasks, and setting up firewalls.